Increased oxidative stress in injured and ill elite international Olympic rowers - Lewis, N. A.; Simpkin, A. J.; Moseley, S.; Turner, G.; Homer, M.; Redgrave, A.; Pedlar, C. R.; Burden, R. (International Journal of Sports Physiology and Performance, 2020)
Background: Identifying strategies that reduce the risk of illness and injury is an objective of sports science and medicine teams. No studies have examined the relationship between oxidative stress (OS) and illness or injury in international athletes undergoing periods of intensified training and competition. Purpose: The authors aimed to identify relationships between illness, injury, and OS. Methods: A longitudinal, observational study of elite male rowers (n=10) was conducted over 18 weeks, leading into World Championships. Following a recovery day and a 12-hour fast, hydroperoxides (free oxygen radicals test) and total antioxidant capacity (free oxygen radicals defense) were measured in venous blood, with the ratio calculated as the oxidative stress index (OSI). At all study time points, athletes were independently dichotomized as ill or not ill, injured or not injured. OS data were compared between groups using independent t tests. A Cox proportional hazard model was used to assess the association of OS with injury and illness while adjusting for age and body mass index. Results: Free oxygen radicals defense was lower (P<.02) and OSI was higher (P<.001) with illness than without illness. Free oxygen radicals test and OSI were higher with injury than without injury (P<.001). A 0.5 mmol/L increase in free oxygen radicals defense was associated with a 30.6% illness risk reduction (95% confidence interval, 7%-48%, P=.014), whereas 0.5 unit increase in OSI was related to a 11.3% increased illness risk (95% confidence interval, 1%-23%, P=.036). Conclusions: OS is increased in injured and ill athletes. Monitoring OS may be advantageous in assessing recovery from and in reducing injury and illness risk given the association.